2012
DOI: 10.1088/2041-8205/760/1/l15
|View full text |Cite
|
Sign up to set email alerts
|

No Clear Submillimeter Signature of Suppressed Star Formation Among X-Ray Luminous Active Galactic Nuclei

Abstract: Many theoretical models require powerful active galactic nuclei (AGNs) to suppress star formation in distant galaxies and reproduce the observed properties of today's massive galaxies. A recent study based on Herschel-SPIRE submillimeter observations claimed to provide direct support for this picture, reporting a significant decrease in the mean star formation rates (SFRs) of the most luminous AGNs (L X > 10 44 erg s −1 ) at z ≈ 1-3 in the Chandra Deep Field-North (CDF-N). In this Letter, we extend these resul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
108
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 166 publications
(123 citation statements)
references
References 45 publications
12
108
3
Order By: Relevance
“…These results argue for a scenario in which powerful quasars, on average, have not yet suppressed the star formation in the host galaxy (see e.g. Harrison et al 2012;Rosario et al 2013;Stanley et al 2015 but also e.g. Page et al 2012).…”
Section: The Star Formation Dependence On Agn Activitymentioning
confidence: 86%
See 2 more Smart Citations
“…These results argue for a scenario in which powerful quasars, on average, have not yet suppressed the star formation in the host galaxy (see e.g. Harrison et al 2012;Rosario et al 2013;Stanley et al 2015 but also e.g. Page et al 2012).…”
Section: The Star Formation Dependence On Agn Activitymentioning
confidence: 86%
“…Shao et al 2010;Harrison et al 2012;Mullaney et al 2012b;Rovilos et al 2012;Santini et al 2012;Rosario et al 2013). They suggest that the sSFRs of AGN are consistent with those of star-forming galaxies, with possible exceptions the luminous AGN (e.g.…”
Section: The Star Formation Dependence On Agn Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies have found a reasonably flat relationship between AGN luminosity and SFR (e.g. Harrison et al 2012;Rosario et al 2012;Azadi et al 2015;Stanley et al 2015). At modest X-ray luminosities where large samples of X-ray AGN with far-infrared and submillimeter data now exist, these results are now robust.…”
Section: X-ray Luminositymentioning
confidence: 86%
“…More recently, new data at far-infrared wavelengths from the Herschel Space Observatory, has been used to study the connection between star formation in galaxies and accretion on to the central AGN (e.g. Lutz et al 2008;Shao et al 2010;Bonfield et al 2011;Harrison et al 2012;Mullaney et al 2012;Page et al 2012;Rosario et al 2012;Rovilos et al 2012;Santini et al 2012;Azadi et al 2014;Stanley et al 2015). Lutz et al (2010) have also conducted a study of the 870-μm properties of z ∼ 1 AGN using LABOCA.…”
mentioning
confidence: 99%